Student's Use of English in German Lessons - Miroslav Janík (Karolinum Press, 2018)
In language learning, teachers often encounter multilingualism when teaching a specific language. Multilingualism is the ability to use languages in an interconnected way; languages as such can be thus approached rather as a linguistic repertoire. In this study, we look at how students (and teachers) in Czech schools deal with English use within German lessons. In this context English is the first foreign language taught to students and German the second foreign tongue taught in school. Twenty-eight lessons from four experienced language teachers were recorded at lower-secondary level. Conversational analysis of transcripts identified 65 instances of English use in German classes. The analysis suggests that English is used in three ways, either it is seen as a source of a problem that needs to be repaired, it is accepted practice, or the use of Eng- lish is initiated by the teacher. Our analysis suggests that using English language in German lessons and potentially multilingualism in teaching does not have a clearly defined status. Furthermore, inconsistency in teacher responses to multilingualism may require clearer consideration as to if languages are taught as discreet entities or more flexible linguistic mechanisms may be adopted to facilitate learning.